Clustering and Principal Component Analysis of Nerica Mutant Rice Lines Growing Under Rainfed Condition - Nuruzzaman, Md.; Rana, Md. Shohel; Ferdausi, Aleya; Huda, Md. Monjurul; Hassan, Lutful; Begum, Shamsun Nahar (International Journal of Applied Sciences and Biotechnology, 2019)
A field experiment was conducted at subtropical region in Bangladesh to assess the contribution of morphological traits to variability in some NERICA mutant rice lines. The experiment was conducted following RCBD with three replications. Thirty-one NERICA rice genotypes (twenty-eight mutant lines along with three parents) of advanced generations were used. Data were collected on twelve morphological traits. The results of the principal component analysis showed that the first four components account for 80% of total variation giving a clear idea of the structure underlying the variables analyzed. This result was also supported by scree test. Cluster analysis using Ward’s method classified the thirty-one genotypes into five distinct groups. The maximum inter-cluster distance was observed between clusters indicating the possibility of high heterosis if individuals from these clusters are cross-bred. The results of PCA were closely in line with those of the cluster analysis. These results can now be used by breeders to develop drought tolerant high yielding rice varieties and new breeding protocols for rice improvement. Int. J. Appl. Sci. Biotechnol. Vol 7(3): 327-334